A narrativa de Odette de Barros Mott e a formação do subsistema juvenil na literatura brasileira - Elias, Ieda Maria Sorgi Pinhaz (2015)
The objective of this dissertation is, from the systematic collection of critical fortune as well as Odette de Barros Mott (1903-1998) works cataloguing, to understand her importance and participation on the Brazilian juvenile literary subsystem through features concerning the formation novel, Bildungsroman, in the narrative: Justin, theretirante (1970).The accomplishment of this work is justified by the necessity to investigate the juvenile literary production in Brazil, since it still lacks this kind of study, besides the contributions offered to teachers who use theauthor's texts. The theoretical foundations of this work is grounded on the reading Sociology, with contributions of Antonio Candido (1976, 1988), Robert Escarpit (1974), Literary History and Literary Theory - Marisa Lajolo e Regina Zilberman (1984,1988), psychology and sociology of adolescents - LuísAntônioGroppo (2000) Guillermo Obiols (2006), Literary History - EdmirPerrotti (1986), the role of cultural industry - Pierre Bourdieu (2007), Theory of Reception - Hans Robert Jauss (1994), in literary theory - Antoine Campagnon (2010), as well as on the concepts from formation novel - Bildungsroman, with the studies of Wilma Patrícia Maas (2000), all of which are outstanding so that we could reach our objectives. The outcomes led to the perception that Odette de Barros Mott not only contributed so that the juvenile literary production had nationwide representation, but was also the forerunner of realism in novels aimed at youth, thus promoting through her texts discussions on taboo subjects, specially in the seventies.